Imagery and Arguments Pertaining to the Issue of Free Immigration in the Anglo-Irish Press in Rio de Janeiro - Araujo Neto, Miguel Alexandre de (ABEI Journal, 2003)
This paper will examine the early relationship between a mid – to late nineteenth century Anglo-Irish newspaper, ‘The Anglo-Brazilian Times’ (1865- 1884), and the political élites of the Brazilian Second Empire (1840-1889). The argumentation departs from the hypothesis that Great Britain, from around 1865 onwards, had devised a plan whereby Brazil would be persuaded into abolishing slavery through the liberalization of her immigration policy. This way, the massive introduction of Europeans into the country would render slavery obsolete. The activities of the editor and proprietor of that newspaper, the Irish- born journalist William Scully, look consistent with that course of action and seem to have relied at least partially on the financial support of the British Government. This strategy was short-lived and seems to have generated a serious political crisis in Brazil, which would have accounted for the failure of an English-speaking colony that was established on the margins of the Itajahy- Mirim river valley, in 1867, in the southern Brazilian province of Santa Catarina. That colony was partially occupied by Irish settlers introduced in Brazil in connection with Scully.